EFEKTIVITAS PROGRAM PENATAAN PARKIR DI KAWASAN PUSAT OLEH-OLEH PANDANARAN KOTA SEMARANG - Rahma, Arini Alfia; Warsono, Hardi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Semarang Government has set regulations prohibition of parking in the central of souvenirs store Pandanaran Semarang based on Undang-undang Lalu Lintas Aturan Jalan number 22 year 2009 and regional regulation of Semarang City number 1 year 2004 about Penyelenggaraan dan Retribusi Parkir di Tepi Jalan Umum. This regulation start from 2014 to reduce the problems of congestion and undisciplined traffic in the central of souvenirs store Pandanaran Semarang. However now, transgressor still found frequently, and author wants to do related research about the effectiveness of parking arrangement program also factors which give influence to effectiveness of the program. Method of this research is descriptive, with qualitative approach. The result of this study show that the parking arrangement program is effective enough to reduce congestion although was not maximal, because congestion is also caused by high-volume vehicles that pass. Furthermore, the factors that influence can be seen from two factors, infrastructure and society behavior. In terms of infrastructure, Semarang Government has provided infrastructure that support the parking arrangement program specifically parking lot and free shuttle bus, while in terms of society behavior shall have high awareness to not parked their vehicles into the side of road. Recommendation for Semarang Government shall improve socialization about parking arrangement program and infrastructure which provided and shall give firm punishment to deterrent violators.